Family Experiences of Mental Illness: A Meta-Synthesis - Panes, Iril I; Tuppal, Cyruz P; Baua, Ma Elizabeth P; Vega, Paolo D; ReÃ±osa, Mark Donald C (Department of Nursing, Faculty of Medicine, Diponegoro University, 2018)
Background: Caring for a family member diagnosed with mental illness requires a holistic support system. However, some families experience the feeling of burden, loss, and stigma affecting the entire family structure. Therefore, exploring the studies on the family experiences of mental illness is crucial.Purpose: This meta-synthesis explored the available literature on the family experiences of mental illness.Methods: An initial comprehensive search was conducted in the following databases such as Web of Science, Scopus, PsycINFO, CINAHL and Ovid-based MEDLINE using the keywords like mental illness, mental disorder, family, family member, qualitative studies and phenomenology. A total of five qualitative studies and one thesis dissertation published between 2001-2016 that elicited views of family members on their experience of mental illness were reviewed. A thematic analysis was used to identify, analyze, and report patterns among the data, allowing for specific organization and description and interpretations.Results: Family empowerment emerged as the grand theme from the perceived effects of mental illness on the family, the process of coping and their perspectives on family empowerment grounded on family experiences.Conclusion: Despite caring for a family member diagnosed with mental illness imposes threats, it further offers openness, readiness, and acceptance that empower each family to appreciate, acknowledge, and affirm the wholeness of a family member with mental illness.